Pengaruh Kemandirian terhadap Kinerja Penyuluh Pertanian PNS di Provinsi Riau (Studi Kasus di Kota Dumai dan Kabupaten Siak): Pengaruh Kemandirian terhadap Kinerja - Novika Sari Harahap (Balai Pelatihan Pertanian Jambi, 2023)
This paper discusses the effect of independence on the performance of civil servant agricultural extension workers in Riau Province (Case Studies in Dumai City and Siak Regency). This research uses instruments in the form of: Primary data obtained by structured interview techniques with tools in the form of questionnaires and documentation tools. Questionnaires used for data collection, validity and reliability tests were carried out Research to determine the elements of independence that affect the performance of civil servant extension workers. Elements of independence include material/economic independence, intellectual independence, emotional independence, and social independence.